Biogas purification on Na-X Zeolite: Experimental and numerical results. (21st September 2020) - Bareschino, Piero; Mancusi, Erasmo; Forgione, Annunziata; Pepe, Francesco
Highlights: H2S adsorption in a packed bed Na-X zeolite was experimentally studied and modelled. Bed complete saturation could never be achieved as a consequence of H2S oxidation. Bed H2S adsorption capacity decreases with aging as a result of sulfur poisoning. A 1-D mathematical model able to describe the observed behaviour was developed. Physical parameters governing H2S reactive adsorption were consequently established. Abstract: In the present paper, H2 S adsorption from a synthetic biogas mixture in a laboratory–scale fixed bed adsorption column was studied and modelled. Na–X zeolite was used as bed material. Breakthrough and equilibrium data were obtained in a number of experiments carried out under typical operating conditions of industrial applications. Experimental results show that complete saturation of the bed could never be achieved, since outlet H2 S concentration approaches an asymptotic value always lower than inlet one as a consequence of catalytic oxidation reactions of hydrogen sulphide. A one-dimensional coupled heat and mass transfer model, based on the "linear driving force" assumption and accounting for both H2 S oxidation reaction and zeolite deactivation due to sulfur poisoning, was purposely developed and tailored to match experimental results. Consequently, the assessment of the effects of variation in H2 S concentration, adsorption temperature and adsorbent age on the performances of the removal process was carried out.